Transforming Teachers’ Roles in Navigating the Challenges of Implementing the Independent Curriculum: Adaptive Strategies and Professional Reflection in Elementary School - Yeyen Fitri; Lud Waluyo; Iis Siti Aisyah (Journal Evaluation in Education (JEE), 2025)
Purpose of the study: This research aims to examine the transformation of teachers' roles in facing the challenges of implementing the Independent Curriculum in elementary schools and understand how teachers adapt to these educational changes. Methodology: This study uses a descriptive qualitative approach with exploratory case study design. Data collection methods include direct classroom observation, in-depth interviews, and documentation studies involving teachers actively implementing the Independent Curriculum in elementary schools. Main Findings: Teachers face significant obstacles in understanding learning outcomes, implementing project-based learning, and utilizing learning technology optimally. Despite available training programs, teacher participation remains sporadic with limited impact on practice changes. Teachers respond through self-training strategies, informal collaboration, and pedagogical reflection, though lacking institutional mentoring support. Role transformation occurs contextually and gradually, depending on individual initiative and school environment support. Novelty/Originality of this study: This research contributes by uncovering teacher role dynamics in marginalized schools previously underexplored in Independent Curriculum studies, providing insights for developing contextual, collaborative, and sustainable teacher capacity building policies.